An analysis of the combination frequencies of constituent medicinal herbs in prescriptions for the treatment of bone and joint disorder in Korean medicine: determination of a group of candidate prescriptions for universal use - Yoo Kyoung Han; Seo Yul Kim; Jae Young Ahn; Jin Ung Baek (Integrative Medicine Research)
Background: This study aimed to select prescriptions (mixtures of medicinal herbs) used in the treatment of bone and joint disorders in Korean medicine, and through the analysis of medicinal herb combination frequencies, select a high-frequency medicinal herb combination group for further experimental and clinical research. Methods: We systematically searched for terms related to bone and joint disorder in the âDongeuibogam (Dong yibaojian)â, a seminal Korean medicine book. We reviewed the results of published papers regarding the effects in bone and joint disorders (especially in osteoporosis, osteomalacia, osteopenia, rheumatoid arthritis, and degenerative arthritis). Results: In total, 34 candidates of a medicinal herb combination for the treatment of bone and joint disorders(CMHCTBJDs) and nine candidates of a medicinal herb for the treatment of bone and joint disorders(CMHTBJDs) were selected. Conclusion: : The candidates of a medicinal herb combination for the treatment of bone and joint disorders (CMHCTBJDs) and candidates of a medicinal herb for the treatment of bone and joint disorders(CMHTBJDs) proposed in this study can be useful material for text mining to develop natural products with the effects in BJDs and also it has the potential to reduce the experimental and developmental time period. Keywords: Dongeuibogam (Dong yi bao gian), Text mining, Bone disorder